2022
DOI: 10.55519/jamc-04-s4-9885
|View full text |Cite
|
Sign up to set email alerts
|

Response to Immunosuppressive Therapy in Patients of Acquired Aplastic Anaemia: A Single Center Experience From a Developing Country

Abstract: Background: Aplastic Anaemia (AA) is characterized by pancytopenia and hypocellular marrow. Immunosuppressive therapy (IST) SHOWS impressive haematological response; however, risk of relapse and clonal evolution persists. The objective of the study is to assess response to IST in patients with aplastic anaemia. Methods: A retrospective single centre study at AFBMTC / NIBMT for patients of acquired AA was conducted from January 2005 to December 2019.Inclusion criteria included diagnosed cases of acquired AA rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This high prevalence in younger age groups can be attributed in part to the demography of the country, with 19.3% and 34.7% of the population falling into the age groups of 15-24 years and <15 years respectively [ 23 ]. Male patients predominated in Asian countries according to studies [ 24 ]. Our cohort had a male-to-female ratio of 2.3:1, which aligns with previous studies from the region [ 24 - 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high prevalence in younger age groups can be attributed in part to the demography of the country, with 19.3% and 34.7% of the population falling into the age groups of 15-24 years and <15 years respectively [ 23 ]. Male patients predominated in Asian countries according to studies [ 24 ]. Our cohort had a male-to-female ratio of 2.3:1, which aligns with previous studies from the region [ 24 - 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male patients predominated in Asian countries according to studies [ 24 ]. Our cohort had a male-to-female ratio of 2.3:1, which aligns with previous studies from the region [ 24 - 26 ]. The apparent high number of males in our study (70.1%) could be due to social biases since men are more valued in our society and hence receive preferential treatment in terms of medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen acquired aplastic anemia linked to environmental causes is higher in Southeast Asia, where industrial and agricultural operations expose a large population to chemicals, poisons, fertilizers, and pesticides.19 Acquired aplastic anemia linked to autoimmune disorders and infections is more prevalent in highly populated urban regions with few tertiary healthcare services (Killick et al, 2016). A higher frequency of drugassociated acquired aplastic anemia is linked to the overthe-counter availability of antibiotics and analgesics without a prescription in undeveloped rural areas with inadequate primary health services (Ehsan et al, 2011;Killick et al, 2016). Southeast Asian countries have higher rates of environmental pollution since fewer eco-friendly cars are on the road and industrial waste is poorly handled (Rathore et al, 2014).…”
Section: Gendermentioning
confidence: 99%
“…Drug use and viral hepatitis were frequent risk factors, which is in line with prior research that has reported occurrences of aplastic anemia with no known cause. Acquired aplastic anemia has been linked to drugs and hepatitis B&C infections in several studies (Ehsan et al, 2011;Killick et al, 2016).…”
Section: Gendermentioning
confidence: 99%